Dimension growth of Azadirachta excelsa and Phyllanthus spp. in agroforestry system - NILASARI DEWI; NURHENI WIJAYANTO; GUSMAINI GUSMAINI (Biodiversitas Journal of Biological Diversity, 2017)
Dewi N, Wijayanto N, Gusmaini. 2017. Dimension growth of Azadirachta excelsa and Phyllanthus spp. in agroforestry system. Biodiversitas 18: 494-499. Azadirachta excelsa Jack. is one of the fast growing species which have high resistance to pest and disease, good quality of wood, and high economic value. A. excelsa planting can be integrated with Phyllanthus spp. in agroforestry system. The research about meniran and sentang in agroforestry system was conducted to analyze the influence of A. excelsa allelopathy towards the growth of meniran and to analyze the growth of both plants. This research was conducted for six months in Bogor, West Java. This study was divided into three parts, (i) analyze the effect of allelopathy in A. excelsa leaf and twig on the growth of P. urinaria and Phyllanthus debilis, (ii) analyze the growth of A. excelsa in monoculture and agroforestry systems and (iii) analyze the growth of meniran in monoculture and agroforestry systems. The result showed that leaf and twigs litter of A. excelsa did not have negative allelopathic effect for the growth of P. urinaria and P. debilis. Agroforestry system did not give significant effect to the growth of A. excelsa . Agroforestry systems reduced the growth of both P. urinaria and P. debilis due to light deficiency.